Rainy and dry seasons impact on electricity demand in Indonesia - Hasibuan, Arnawan; Nrartha, I Made Ari; Fithra, Herman; Desky, Muhammad Aulia; Isa, Muzamir; Siregar, Widyana Verawaty; Nurdin, Nurdin; Kurniawan, Robi (SINERGI, 2024)
Electricity consumption has become an integral part of daily life and is pivotal in supporting various aspects of human life. North Aceh Regency, a tropical region in Indonesia, experiences significant seasonal fluctuations between the rainy and dry seasons. This research aims to investigate and analyze the impact of these seasonal differences on electricity consumption patterns by consumers in the region using the IBM SPSS statistical method. Monthly electricity consumption data from consumers in North Aceh Regency over a specific period were collected and analyzed using IBM SPSS software. Descriptive statistical analysis, hypothesis testing, and regression models were employed to identify significant differences in electricity consumption between the rainy and dry seasons and to understand the factors influencing consumption patterns. The results of the analysis indicate a significant difference in electricity consumption between the rainy and dry seasons in North Aceh Regency. The dry season shows an increase in electricity consumption, possibly related to factors such as the use of air conditioning and additional lighting.